Experimental and Modeling Study of Melt Polycondensation Process of PA‐MXD6. Issue 1 (November 2013) - Xi, Zhenhao; Chen, Like; Zhao, Yong; Zhao, Ling; Moritz, Hans‐Ulrich; Pauer, Werner
Summary The main polycondensation reaction of poly(m‐xylene adipamide) (PA‐MXD6) is a reversible reaction strongly coupled with mass transfer in melt polycondensation process. In this work, a realistic model for melt polycondensation of PA‐MXD6 has been proposed taking in to account the kinetics data, equilibrium data and diffusion process for major by‐product water in the melts. The characteristics of reaction and the effects of mass‐transfer of polycondensation process have been studied by using stagnant film experiments. It is observed that the apparent rate of the polycondensation process increases with higher temperature, lower degree of vacuum and thinner film thickness with reduced specific interfacial area. Based on the experimental data, the model parameters including the kinetics data, equilibrium data and mass transfer coefficient of volatile have been estimated by the nonlinear least squares method. The model predictions are in a quite satisfactory agreement with the experimental data that all of the relative deviations are almost less than 2%.